Spatial characteristics of urban square and sociability: a review of the City Square, Melbourne - Zakariya, Khalilah; Harun, Nor Zalina; Mansor, Mazlina (Elsevier, 2014)
Public squares function as open spaces where people can conduct many activities and events in the city. The ‘life’ of squares evolves and changes according to the contemporary demands of the people. Learning from the evolution of the City Square in Melbourne, Australia, this study aims to analyse how its designs changed over the years in order to accommodate city life. This study employs spatial analysis to examine the relationships between the square’s physical characteristics with people’s activities. The findings reveal that square designs ought to meet evolving social, physical and environmental needs to cater for future requirements and lifestyles.